The Roles and Existence of Fisherwoman in Indonesian Women's Development - Triyant,; Hartanto, Rima Vien Permata (International Journal of Psychosocial Rehabilitation, 2020)
This study discusses the recognition of the entities and capabilities of fisherwoman in Bonang Subdistrict, Demak Regency, Central Java, Indonesia. In general, this study examines the impact of the presence of fisherwoman on women's development specifically and human development in Indonesia. Paradigmatically, this study relies on the Sotirios Sarantakos category called the critical paradigm with socio- legal or non-doctrinal research. The findings of this study state that fisherwoman have important roles and contributions both in the production and non-production cycles of fisheries and development. However, the role and contribution of fisherwoman in fisheries and national development are not recognized and have not been accommodated in local and national policies. Neglecting the role and contribution of fisherwoman means keeping women away from control and access to development programs.